The application of x-ray fluorescence spectrometry for multielemental analysis of air particulate samples - Mohd. Yusof, Mohd. Rashid (1986)
The performance of XRF spectrometer as a tool for multielemental analysis for air pollution samples was discussed. The non-destructive couples with multielemental nature of the technique and satisfactory sensitivity for most elements were the most important characteristics for its popularity as a method of analysis. Thus, the technique promises a significance reduction in cost and time of analysis. As a result, more extensive and revealing air particulates survey should be possible, with consequent improvements in the discovery and positive identification of particulate pollution sources.